Penerapan Akuntabilitas terhadap Realisasi Anggaran Dana Bantuan Operasional Sekolah (BOS) di Sekolah Dasar Swasta Islam Terpadu Ibu Harapan Bengkalis - Kiki Candri; Mashuri Mashuri; Sri Rahmany; Iswandi Iswandi (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2024)
This study aims to determine the accountability for the realization of the school operational assistance fund budget at the Integrated Islamic Private Elementary School Ibu Harapan Bengkalis. This study uses a descriptive qualitative research method where data collection uses interview and documentation techniques. The test results show that accountability for the realization of the school operational assistance fund budget has not been carried out perfectly, due to several factors that have caused this to happen. So that the accountability of the financial reports produced is not in accordance with the technical instructions for the School Operational Assistance (BOS) guidelines.